Building in room to fail: Learning through play in an undergraduate course - Hannah Gascho Rempel (University of Huddersfield Press, 2022)
True learning happens when we try new things - when we practice something, see how it goes, and then try it again. Pedagogical practices that encourage metacognition and active reflection are built on this premise. But these practices take time, and university instructors are pressured to cover as much content as possible in a term. Practice also feels like a luxury to students who receive few opportunities for evaluative feedback, and who don't want to sacrifice a good grade for the sake of trying something new. As a result, learners tend to play it safe. But when the skills of metacognition are presented through the lens of play, which encourages and builds in room for graceful failure, learners become more open to reflective practices and experimentation. In a term-long course for undergraduates entitled 'Learning Through Play', I introduce learners to an information literacy-based research process while using the language and theories of play. Learners ultimately build their own game, but along the way, they practice key elements of the research process: exploring and researching a topic from multiple angles; reading the scholarly literature in a scaffolded manner; and using relevant background information to create something new. I lead class-wide games to help reinforce these topics, and students adapt and lead games in small groups to practice experimentation and cooperation. In this article, I share my course design, the theories underpinning this approach to learning, and suggestions for others who might want to teach a similar course.